2022
DOI: 10.3390/ijerph192013329
|View full text |Cite
|
Sign up to set email alerts
|

Do Land Use Structure Changes Impact Regional Carbon Emissions? A Spatial Econometric Study in Sichuan Basin, China

Abstract: Human activities are closely related to carbon emissions and the mechanism of land-use structure change on carbon emissions is unclear. In this study, 143 counties in the Sichuan Basin of China were used as sample units, and the land use structure of each sample unit in the Sichuan Basin was measured by applying the information entropy theory, analyzing the spatial and temporal evolutionary characteristics and the influencing relationships of land use structure and carbon emissions in the Sichuan Basin, by spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…According to this study’s findings, which are consistent with those of earlier studies [ 22 , 46 ], construction land is the primary carbon source, whereas forest lands provide the strongest carbon sequestration processes. This study discovers that net carbon emissions in the Yellow River Basin have an obvious spatial link and that the spatial distribution follows a southeast-to-northwest pattern, which is in accordance with the opinions of academics such as Ma Yuan [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to this study’s findings, which are consistent with those of earlier studies [ 22 , 46 ], construction land is the primary carbon source, whereas forest lands provide the strongest carbon sequestration processes. This study discovers that net carbon emissions in the Yellow River Basin have an obvious spatial link and that the spatial distribution follows a southeast-to-northwest pattern, which is in accordance with the opinions of academics such as Ma Yuan [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Then, the Canadian scholar Thakur applied it into geography [54]. On this basis, scholars used information entropy to analyze the land use structure at different scales [55][56][57]. For example, Fan et al suggested that the volatility of LUCC can be reflected by information entropy [58].…”
Section: Information Entropy and Mixed Land Usementioning
confidence: 99%
“…Currently, the use of remote sensing technology to investigate LUCC has been the first option for many academics because continuously developing remote sensing technology offers a new technological means for LUCC research, which is essential in this field 26 30 The dynamic degree, 31 33 transition matrix model, 34 36 land use extent composite index model, 35 , 37 land-use structure information entropy, 38 spatial autocorrelation analysis, 39 41 and other indicators and methods have been used to study LUCC. Advancing research can provide a deeper understanding of the evolutionary process of land-use development, with some statistical models that are able to simulate future trends of land-use change emerging, such as future land-use simulation 42 , 43 and land use and its effects 44 , 45 .…”
Section: Introductionmentioning
confidence: 99%